A Chinese Traditional Therapy for Bleomycin-Induced Pulmonary Fibrosis in Mice - Lifang Sun; Minjie Mao; Zhisheng Yan; Cuiyun Zuo; Xiaojie Zhang (Canadian Respiratory Journal)
Pulmonary fibrosis is a chronic and fatal disease of lung tissue with high incidence and mortality in the world. The exploration of effective treatment for pulmonary fibrosis remains an urgent challenge. In our study, Qingfei Xieding was investigated as a novel Chinese traditional patent medicine against pulmonary fibrosis. A pulmonary fibrosis mouse model was constructed by injecting with bleomycin sulfate. Following Qingfei Xieding administration, lung samples were collected to assess pulmonary phenotype changes by analyzing lung coefficient, wet/dry, and histopathologic section. Levels of nitric oxide (NO), hydroxyproline (HYP), malondialdehyde (MDA), and total antioxidant capacity were measured to evaluate the degree of oxidation. A single-cell gel electrophoresis (SCGE) assay was used to evaluate bleomycin-induced DNA damage. Western blotting and real-time quantitative PCR were performed to determine the abundance of inducible nitric oxide synthase (iNOS), connective tissue growth factor (CTGF), alpha smooth muscle actin (α-SMA), and fibronectin (FN). In the present study, Qingfei Xieding administration significantly attenuated bleomycin-induced pulmonary fibrosis in mice by reducing lung coefficient, wet/dry, NO, HYP, and MDA as well as the expression of iNOS, CTGF, α-SMA, FN, and DNA damage. The results indicated that Qingfei Xieding is effective to resist oxidative damage and histopathologic lesion, serving a protection role on bleomycin-induced pulmonary fibrosis.